Analisis Waktu Tunggu Pelayanan Poliklinik Paru di Rumah Sakit Umum Daerah (RSUD) Tangerang - Mahadewi, Erlina Puspitaloka; Heryana, Ade; Kurniawati, Yatmi; Ayuba, Iyan (Universitas Gorontalo, 2019)
Service queue is a clasically service problem at hospital. The conotation of patient queue both positive and negative. When the patients more prefer to our services, it’s a positive matter. But when patients forced to waiting the service because the length of service time, it’s a negative matter. It’s suggested that the increasing of inpatients service affected to outpatients, because doctors who served often late to outpatient services room. This condition led to patient’s unsatisfaction due to unappropriateness of service time standards. This study aimed to analyze the determinants of length of outpatient services waiting time who served by pulmonologist at general hospital Tangerang City. Qualitative design was held to get deepest information about length of pulmologist service time. Five informants were recruited i.e outpatient service coordinator, nurse, pulmonologist, and two patients who complained to length of waiting time. Result there were conditions that affected the length of service time i.e lack of nurse skill particularly in spirometre operation, inadequately amount of chair at waiting room and trobleshooting of information system, unavailable of service procedure that led to imprecise of newly patient service, working condition wasn’t support to pulomonogist service i.e inpatient service activity. It’s suggested to complete with procedure operation standard and enhance infrastructure budget to update the information system and the addition of chairs at waiting room.pelayanan rawat jalan akibat petugas terlambat datang ke poliklinik. Hal ini berdampak pada ketidakpuasan pasien karena ketidaksesuaian dari standar yang telah ditetapkan. Atas dasar itulah maka menarik untuk diadakan penelitian tentang faktor penyebab lamanya waktu tunggu pelayanan rawat jalan. Penelitian ini bertujuan untuk mengetahui penyebab lamanya waktu tunggu pasien di Pelayanan Rawat Jalan Poliklinik Penyakit Paru RSUD Kota Tangerang. Penelitian ini menggunakan pendekatan kualitatif dengan tujuan mendapatkan informasi yang lebih aktual dan akurat mengenai faktor penyebab lamanya waktu tunggu di Pelayanan Rawat Jalan Poliklinik Paru RSUD Kota Tangerang. Informan terdiri dari informan kunci, informan utama dan informan pendukung. Gambaran penyebab lamanya waktu tunggu pelayananan di bagian Instalasi Rawat Jalan dalam pelayanan di Poliklinik Paru RSUD Kota Tangerang, yaitu: perawat masih memerlukan pelatihan dan pengembangan dalam mengoperasikan alat spirometri, fasilitas ruang tunggu yaitu kursi yang masih belum mencukupi dan program SIMRS (system infromasi manajemen Rumah Sakit) yang harus lebih baik lagi untuk menunjang kegiatan di pelayanan poliklinik paru, prosedur pemberian pelayanan masih belum lengkap, SOP (Standar Operasional Prosedur) alur pelayanan belum ditetapkan, sehingga pada pasien baru sering terjadi salah prosedur, tingginya jumlah tindakan pasien paru rawat inap menyebabkan lamanya pelayanan. Saran sebaiknya manajemen rumah sakit melengkapi SOP pada instalasi rawat jalan, penambahan anggaran terkait pembaharuan SIMRS dan penambahan fasilitas tempat duduk pasien.